Plantar pressure distribution under uniform and gradient foam during running and jumping - Duncan, O.; Naylor, G.; Godfrey, J.; Allen, T.; Foster, L.; Hart, J.; Alderson, A. (Proceedings, 2020)
Auxetic materials have a negative Poisson`s ratio, meaning they contract laterally during axial compression. Auxetics can also absorb more energy during impacts than conventional materials. Auxetic foam was fabricated by volumetrically compressing open cell foam to buckle cell ribs and impart a re-entrant cell structure, then the imposed structure was fixed by heating and cooling. Passing pins through the foam allowed localised control over compression during fabrication, producing gradient foam with regions with differing Poisson`s ratios and stress vs. strain relationships. Uniform sheets had volumetric compression ratios of three, gradient sheets had volumetric compression ratios of one (unchanged) or three in different regions. One participant jumped barefoot on all foams, cut out to fit pressure sensors; another ran wearing shoes containing uniform converted and unconverted foam insoles. Pressure distribution was measured underneath the foams and foam insoles. Peak pressure was lowest underneath converted foams, warranting further investigation with more participants.